Sustaining development through socio-economic rights : prospect and challenges in selected African countries - Maidin, Ainul Jaria; Sambo, A.O.; Ansari, Abdul Haseeb; Abdulkadir, A.B. (American-Eurasian Network for Scientific Information (AENSI), Jordan, 2011)
One of the most nagging problems in Africa today in general and countries under review in particular is the struggle for sustainable development. The paper discusses this aspect and contends that sustainable development in the countries under review is achievable through adequate protection of socio-economic rights. There are, however, prospects and some challenges for sustaining development through the instrumentality of socioeconomic rights. The paper makes an analytical exposition of these challenges and hypothesizes that if these challenges are surmounted, the countries will experience sustainable development through adequate protection of socio-economic rights.